A Novel Role of the L-Type Calcium Channel α1D Subunit as a Gatekeeper for Intracellular Zinc Signaling: Zinc Wave - Yamasaki, Satoru; Hasegawa, Aiko; Hojyo, Shintaro; Ohashi, Wakana; Fukada, Toshiyuki; Nishida, Keigo; Hirano, Toshio (PLOS ONE, 2012)
Recent studies have shown that zinc ion (Zn) can behave as an intracellular signaling molecule. We previously demonstrated that mast cells stimulated through the high-affinity IgE receptor (FcεRI) rapidly release intracellular Zn from the endoplasmic reticulum (ER), and we named this phenomenon the “Zn wave”. However, the molecules responsible for releasing Zn and the roles of the Zn wave were elusive. Here we identified the pore-forming α1 subunit of the Cav1.3 (α1D) L-type calcium channel (LTCC) as the gatekeeper for the Zn wave. LTCC antagonists inhibited the Zn wave, and an agonist was sufficient to induce it. Notably, α1D was mainly localized to the ER rather than the plasma membrane in mast cells, and the Zn wave was impaired by α1D knockdown. We further found that the LTCC-mediated Zn wave positively controlled cytokine gene induction by enhancing the DNA-binding activity of NF- κB. Consistent with this finding, LTCC antagonists inhibited the cytokine-mediated delayed-type allergic reaction in mice without affecting the immediate-type allergic reaction. These findings indicated that the LTCC α1D subunit located on the ER membrane has a novel function as a gatekeeper for the Zn wave, which is involved in regulating NF-κB signaling and the delayed-type allergic reaction.